Research on thanksgiving education of college students in new era - Qinjuan Ma; Pingshui, Wang (IJRDO- Journal of Educational Research, 2020)
Thanksgiving education is of great significance to cultivate the healthy personality of college students, improve the effectiveness of moral education and construct a harmonious society. In view of the current situation of lack of Thanksgiving consciousness among college students, it is necessary to carry out Thanksgiving education among college students. Therefore, efforts should be made to create a Thanksgiving education atmosphere, establish an effective Thanksgiving practice mechanism, and do a good job in Thanksgiving education.